Tau/MAPT disease-associated variant A152T alters tau function and toxicity via impaired retrograde axonal transport. (26th December 2018) - Butler, Victoria J; Salazar, Dominique A; Soriano-Castell, David; Alves-Ferreira, Miguel; Dennissen, Frank J A; Vohra, Mihir; Oses-Prieto, Juan A; Li, Kathy H; Wang, Austin L; Jing, Beibei; Li, Biao; Groisman, Alex; et al.
Abstract: Mutations in the microtubule-associated protein tau ( MAPT ) underlie multiple neurodegenerative disorders, yet the pathophysiological mechanisms are unclear. A novel variant in MAPT resulting in an alanine to threonine substitution at position 152 (A152T tau) has recently been described as a significant risk factor for both frontotemporal lobar degeneration and Alzheimer's disease. Here we use complementary computational, biochemical, molecular, genetic and imaging approaches in Caenorhabditis elegans and mouse models to interrogate the effects of the A152T variant on tau function. In silico analysis suggests that a threonine at position 152 of tau confers a new phosphorylation site. This finding is borne out by mass spectrometric survey of A152T tau phosphorylation in C. elegans and mouse. Optical pulse-chase experiments of Dendra2-tau demonstrate that A152T tau and phosphomimetic A152E tau exhibit increased diffusion kinetics and the ability to traverse across the axon initial segment more efficiently than wild-type (WT) tau. A C. elegans model of tauopathy reveals that A152T and A152E tau confer patterns of developmental toxicity distinct from WT tau, likely due to differential effects on retrograde axonal transport. These data support a role for phosphorylation of the variant threonine in A152T tau toxicity and suggest a mechanism involving impaired retrograde axonal transport contributing to human neurodegenerative disease.